2018
DOI: 10.3126/jgmcn.v11i1.20789
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Thyroid Lesions with Fine Needle Aspiration Cytology and Thyroid Function Tests

Abstract: Introduction: Swelling of the thyroid gland is a commonly encountered clinical problem in all age groups whether benign or malignant. Fine Needle Aspiration Cytology (FNAC) of the thyroid lesions along with hormonal function test helps in the proper preoperative assessment. Ultimately it changes clinical management and improves the patient outcome.Objectives: To describe the cytomorphological features of palpable thyroid nodules using fine needle aspiration cytology (FNAC) along with the assessment of thyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…Analysing the relationship between thyroid disease and hormonal status, a significant proportion of individuals with colloid goitre (83.33%) maintained euthyroid status. This was consistent with the findings of S. Ranabhat et al [19]. Additionally, V. Jain et al [9] reported a predominant euthyroid status in their patient population (69.1%), followed by hypothyroid (18.8%) and hyperthyroid (12.1%) cases.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Analysing the relationship between thyroid disease and hormonal status, a significant proportion of individuals with colloid goitre (83.33%) maintained euthyroid status. This was consistent with the findings of S. Ranabhat et al [19]. Additionally, V. Jain et al [9] reported a predominant euthyroid status in their patient population (69.1%), followed by hypothyroid (18.8%) and hyperthyroid (12.1%) cases.…”
Section: Discussionsupporting
confidence: 92%
“…In the context of the present study, a substantial majority, accounting for 95% of the cases, exhibited non-neoplastic thyroid lesions, contrasting with 5% of cases characterised as neoplastic. These proportions align closely with findings from S. Ranabhat et al [19], who reported an 88% prevalence of non-neoplastic lesions and a 12% incidence of neoplastic lesions. This consistent pattern is also reflected in the investigation by V. Jain et al [9], where non-neoplastic lesions were more prevalent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation